Use of Combined Irradiation in Grow Light - S. A. Rakutko; E. N. Rakutko; M. R. Ayupov (Сельскохозяйственные машины и технологии)
Effective cultivation of plants with grow light is possible only under optical radiation of a certain spectral composition. The cheapest way to generate optical radiation is with the help of high pressure sodium lamps. However, their spectral composition is not fully acceptable for grow light. LEDs allow you to set almost any spectrum, but their cost is quite high.(Research purpose) To prove the spectral composition of the LED emitter-corrector used in grow light in addition to sodium lamps theoretically and practically.(Materials and methods) The authors experimentally studied the effectiveness of combined irradiation in the Laboratory of Energy Ecology of Grow Light at the Institute of Agroengineering and Environmental Problems of Agricultural Production under the irradiation of Blagovest tomato seedlings. They investigated the biometric indicators of plants. The production experiment was carried out in the greenhouse plant Mezhvidi (Latvia) on adult Encore tomato plants for three options: the first – under sodium lamps; the second – with LED irradiators; the third – with a combination of sodium lamps and corrector. The effect of the irradiator on the plants was evaluated by the magnitude of the fluctuating asymmetry of bilateral signs of the leaf blade.(Results and discussion) The authors found out that the use of the corrector improved the seedlings biometric parameters: increased the number of leaves, their wet weight, the content of chlorophyll and dry substance in them. It was noted that in the greenhouse the least favorable light environment was formed under sodium lamps, and LED irradiators created more comfortable conditions. They confirmed that the use of a corrector provided the best light environment. They revealed an increase in the yield of tomato fruits and their taste when using combined irradiation.(Conclusions) The authors proved that to correct the spectrum of HPS lamp 400, a corrector photon flux of 71.2 micromoles per second is required, while the ratio of blue and far-red LEDs fluxes should be 64 and 36 percent respectively.